Description of Mathematical Creative Thinking and Reasoning Ability of SMP Students in Islamic Culture-Based Learning - Jazuli, Akhmad (EDUCARE, 2013)
ABSTRACT: Learning of Mathematics at the moment seems not to develop studentsâ Mathematical thinking ability to the fullest. Therefore, it is necessary to find solutions to overcome these problems. The purpose of this research is to describe the ability of Mathematical creative thinking and reasoning; and to describe contribution of Islamic culture values to the ability of Mathematical creative thinking and reasoning. This research is qualitative research. TheÂ  subject is the 8th grade students in SMP (Sekolah Memengah Pertama or Junior High School) Al-Irsyad al-Islamiyyah Purwokerto in Central Java, Indonesia; and six students who were selected as respondent. The results research is: (1) the studentsâ ability of Mathematical creative thinking inÂ theÂ high academic achievement category can be said to be complete and very good, the students in the middle academic achievement category can be said to be fair good, deductive reasoning is dominant and creative thinking consist of fluency, originality, and elaboration. The studentsâ ability of Mathematical thinking in the low academic achievement category can be said to be poor, inductive reasoning is dominant and creative thinking only consist of originality component; and (2) the implementation of Islamic culture value gives a positive contribution to âakhlakâ or character building and effectiveness of thinking ability. âTahfizhâ or recitation of Al-Qurâan enhances studentsâ Mathematical higher order thinking ability. The implementation of pray gives studentsâ self confidence and discipline in solving Mathematical problem.KEY WORDS: Mathematical creative thinking, Mathematical reasoning, Islamic culture-based learning, junior high school student, and quality of education.About the Author: Dr. Akhmad Jazuli is a Senior Lecturer at the Department of Mathematics Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto) in Central Java, Indonesia. The author is able to be searched via his e-mail at: jazuli_akhmad@yahoo.comÂ How to cite this article? Jazuli, Akhmad. (2013). âDescription of Mathematical Creative Thinking and Reasoning Ability of SMP Students in Islamic Culture-Based Learningâ in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.81-90. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 11, 2013); Revised (July 22, 2013); and Published (August 17, 2013).Â Â